Analysis of speed, stroke rate, and stroke distance for world-class breaststroke swimming - Garland Fritzdorf, S.; Hibbs, A.; Kleshnev, V. (Journal of Sports Sciences, 2009)
Speed in aquatic locomotion is determined by stroke distance and stroke rate, but it does not always follow that an increase in stroke rate will lead to an increase in speed. Kleshnev (2006) developed a method to evaluate the relationship between speed and stroke rate during rowing - the effective work per stroke. In this case study, the effective work per stroke was determined for a male world-class 100-m breaststroke swimmer for seven races in major championships and compared between: each of the seven races; each quarter within each race; and the best swims of this case study and seven other world-class swimmers. The effective work per stroke was related to race performance, with the fastest race having the highest effective work per stroke and lowest stroke rate, with slower races having low effectiveness and high stroke rate (R2 = 0.85). The effective work per stroke was reduced in a race as the swimmer fatigued. The within-race standard deviation of effectiveness was lower in fast swims (R2 = 0.84). This analysis has identified some characteristics of fast swimming: high effectiveness, optimal stroke rate, and a flat effectiveness profile. Training and racing strategies can now be devised to improve performance by increasing the sensitivity of assessment of strengths and weaknesses in individuals.